Integrating the Local Creative Economy into the Global MICE Value Chain: Evidence from Surakarta - Hasna Wijayati; Haryo Kusumo Aji; Andika Drajat Murdani (CV. RADJA PUBLIKA, 2026)
The creative economy has become an important driver of economic development, particularly within the growing and globally interconnected Meetings, Incentives, Conferences, and Exhibitions (MICE) industry. This study examines how collaboration among local creative economy subsectors supports the integration of Surakarta’s creative economy into the global MICE value chain (GVC). Using a qualitative descriptive approach, data were collected through interviews with key stakeholders and analysis of creative economy and MICE development programs from 2020–2024. The study focuses on patterns of inter-subsector collaboration, institutional facilitation, and their relationship to the global MICE value chain structure. The findings show that collaboration among culinary, craft, performing arts, fashion, and digital media subsectors has strengthened local capacities and supported MICE activities in Surakarta. Local government facilitation has also contributed to coordination, capacity-building, and the readiness of local actors to engage in the MICE industry. However, integration into the global value chain remains limited due to restricted access to international networks, global standards, and partnerships with global MICE actors. Although local collaboration has improved, Surakarta’s creative economy is still positioned at a partial integration stage within the global MICE value chain. This study contributes to GVC literature by emphasizing the importance of local collaboration, institutional support, and global connectivity in strengthening participation in international MICE industries.